2021
DOI: 10.32604/cmc.2021.012454
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Anonymous Authentication Scheme Based on Edge Computing in Internet of Vehicles

Abstract: The vehicular cloud computing is an emerging technology that changes vehicle communication and underlying traf c management applications. However, cloud computing has disadvantages such as high delay, low privacy and high communication cost, which can not meet the needs of realtime interactive information of Internet of vehicles. Ensuring security and privacy in Internet of Vehicles is also regarded as one of its most important challenges. Therefore, in order to ensure the user information security and improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…We found that the attention mechanism improves the model results during our experiments. In the future work, we focus on applying the attention mechanism further to enhance the effects of threat behavior entity extraction and explore the few-shot learning method to improve the classification ability of a few categories and strengthen the generalization ability of the model minor sample problems, and added authentication to enhance the security of the usage process [42].…”
Section: Experimental Results Analysismentioning
confidence: 99%
“…We found that the attention mechanism improves the model results during our experiments. In the future work, we focus on applying the attention mechanism further to enhance the effects of threat behavior entity extraction and explore the few-shot learning method to improve the classification ability of a few categories and strengthen the generalization ability of the model minor sample problems, and added authentication to enhance the security of the usage process [42].…”
Section: Experimental Results Analysismentioning
confidence: 99%
“…To guarantee the safety of data, several works [10,11] built blockchain systems for IoV. Bai et al [12] proposed a driving behavior warning scheme based on blockchain.…”
Section: Application Of Blockchain In the Vehicular Networkmentioning
confidence: 99%
“…The implementation of UAV-assisted MEC systems has some challenges, such as limited onboard energy of the UAV [17], security of aerial data, security of the UAV, data privacy [18], and data management and storage. This study focuses on preserving privacy in UAV-assisted systems.…”
Section: Introductionmentioning
confidence: 99%